Multi-Construct Latent State-Trait Model of Coping with Low-Control Situations - Buško, Vesna (Array, 2004)
Based on the assumptions of the latent state-trait theory (e.g. Steyer, Ferring, & Schmitt, 1992 ; Steyer, Schmitt, & Eid, 1999), the study examines the degree to which variations in situation-specific measures of coping are due to individual dispositions and/or to occasion-related factors. An inventory measuring three broad coping dimensions, i.e., problem solving, acceptance of situation, and emotion-focused coping (e.g. Buško, & Kulenović, 2003), was administered to 421 military basic trainees on two occasions five weeks apart. Several multi-construct latent state-trait models with method factors were tested against the data on the three coping dimensions taken together. The less restrictive version of the model with unequal loadings and within-occasion covariances of the latent state residuals unconstrained across occasions, proved to fit the data best. According to the parameter estimates obtained, the portions of variance attributable to situational and/or interactional effects varied with the point of measurement and the type of coping used. Small but significant within-occasion correlations among the latent state residuals of the three coping constructs were also found, with somewhat more pronounced effects obtained for the second than for the first time point measures. The results are discussed in view of the latent state-trait theory and the processes of coping with low-control stressors.